Early Stone Manipulation in Urinary Tract Infection Associated with Obstructing Nephrolithiasis - Megan L. Swonke; Ali M. Mahmoud; Elias J. Farran; Tamer J. Dafashy; Preston S. Kerr; Christopher D. Kosarek; Joseph Sonstein (Case Reports in Urology)
A urinary tract infection (UTI) and sepsis secondary to an obstructing stone are one of the few true urological emergencies. The accepted management of infected ureteral stones includes emergent decompression of the collecting system as well as antibiotic therapy. Despite this, no consensus guidelines clarify the optimal time to undergo definitive stone management following decompression. Historically, our institution has performed ureteroscopy with laser lithotripsy (URS-LL) treatment at least 1 to 2 weeks after decompression to allow for clinical improvement and completion of an antibiotic course. In this case series, we retrospectively review four cases in which patients had a documented UTI secondary to an obstructive ureteral stone. The patients underwent urgent decompression and, based on labs and clinical improvement, were subsequently treated with URS-LL. The presented patients received URS-LL within 5 days of decompression and antibiotics. The patients had no sepsis related postoperative complications from the accelerated course of treatment, resulting in discharge within 2 days following URS-LL. We provide a detailed examination of each patient presentation to describe our institution’s experience with treating infected kidney stones within days of urgent decompression in order to question the previous standard of treating an infected kidney stone with a more delayed intervention.